1989
DOI: 10.1002/path.1711580305
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of histopathological and flow cytometric parameters in prediction of prognosis in gastric cancer

Abstract: Flow cytometric analysis was performed retrospectively on material from 76 patients having potentially curative resection for gastric carcinoma between 1968 and 1984. The prognostic significance of DNA aneuploidy was compared with that of conventional histological grading and staging of the tumour. The presence of DNA aneuploidy was associated with a significantly poorer prognosis when compared with diploid tumours (P less than 0.02), but was not found to be predictive of survival when the presence of lymph no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 23 publications
3
22
2
Order By: Relevance
“…Furthermore, even in multivariate analysis, DNA ploidy has been shown to be a prognostic factor [51,59,60]. However, some reports have demonstrated that DNA aneuploidy might be associated with a significantly shorter survival only in patients with intestinal-type tumors [61] or only in patients with diffuse-type cancer [62]. Taken together, this evidence strongly supports the hypothesis that aneuploidy is associated with the prognosis of gastric cancer.…”
Section: Gastric Cancer and Dna Aneuploidysupporting
confidence: 64%
“…Furthermore, even in multivariate analysis, DNA ploidy has been shown to be a prognostic factor [51,59,60]. However, some reports have demonstrated that DNA aneuploidy might be associated with a significantly shorter survival only in patients with intestinal-type tumors [61] or only in patients with diffuse-type cancer [62]. Taken together, this evidence strongly supports the hypothesis that aneuploidy is associated with the prognosis of gastric cancer.…”
Section: Gastric Cancer and Dna Aneuploidysupporting
confidence: 64%
“…In stomach cancer, there have been numerous studies correlating DNA flow cytometry with patient prognosis. Several studies showed that patients with stomach cancer with an aneuploid tumour cell population or with a higher proliferative activity had worse prognoses (Tosi et al, 1988;Bronzo et al, 1989;Korenaga et al, 1989;Nanus et al, 1989;Wyatt et al, 1989;Yonemura et al, 1990;Baretton et al, 1991;Kimura and Yonemura, 1991;Johnson Jr et al, 1993;Kakeji et al, 1993;Rugge et al, 1994;Yonemura et al, 1994;D'Agnano et al, 1995;Flyger et al, 1995;Ikeguchi et al, 1995;Sakusabe et al, 1996;Victorzon et al, 1996). Other studies failed to show such correlation (Sasaki et al, 1989;Filipe et al, 1991;Sarbia et al, 1996).…”
mentioning
confidence: 99%
“…They suggested that other factors besides DNA ploidy are responsible for tumor aggressiveness. Filipe et al [7] and Wyatt et al [8] reviewed 116 and 76 cases of gastric carcinoma, respectively, and also failed to find a relationship between DNA ploidy and patient survival.…”
Section: Resultsmentioning
confidence: 95%